2013
DOI: 10.1186/1755-8166-6-4
|View full text |Cite
|
Sign up to set email alerts
|

6p22.3 deletion: report of a patient with autism, severe intellectual disability and electroencephalographic anomalies

Abstract: BackgroundThe interstitial 6p deletions, involving the 6p22-p24 chromosomal region, are rare events characterized by variable phenotypes and no clear genotype-phenotype correlation has been established so far.ResultsHigh resolution array-CGH identified 1 Mb de novo interstitial deletion in 6p22.3 chromosomal region in a patient affected by severe Intellectual Disability (ID), Autism Spectrum Disorders (ASDs), and electroencephalographic anomalies. This deletion includes ATXN1, DTNBP1, JARID2 and MYLIP genes, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Cic-L −/− mice phenocopy Atxn1 −/− ; Atxn1l −/− mice, confirming that these three proteins indeed function as a complex in vivo 9 . Interestingly, large deletions spanning ATXN1 on chromosome 6p22 have been reported in patients with autism spectrum disorder (ASD), developmental delay/intellectual disability (DD/ID), seizures, and attention deficit/hyperactivity disorder (ADHD) 1113 , but it is unclear whether the heterozygous loss of ATXN1 or other genes in the deleted region lead to the clinical presentation. In the case of CIC , two different missense mutations have been reported in two isolated cases of intellectual disability 14,15 , but here again it is unclear whether these variants are causative, because there have been no functional studies to confirm the pathogenicity of the reported missense variants in CIC .…”
Section: Introductionmentioning
confidence: 99%
“…Cic-L −/− mice phenocopy Atxn1 −/− ; Atxn1l −/− mice, confirming that these three proteins indeed function as a complex in vivo 9 . Interestingly, large deletions spanning ATXN1 on chromosome 6p22 have been reported in patients with autism spectrum disorder (ASD), developmental delay/intellectual disability (DD/ID), seizures, and attention deficit/hyperactivity disorder (ADHD) 1113 , but it is unclear whether the heterozygous loss of ATXN1 or other genes in the deleted region lead to the clinical presentation. In the case of CIC , two different missense mutations have been reported in two isolated cases of intellectual disability 14,15 , but here again it is unclear whether these variants are causative, because there have been no functional studies to confirm the pathogenicity of the reported missense variants in CIC .…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis, Fyn was strongly correlated with ATXN1, a DNA-binding protein that forms a transcriptional repressor complex with capicua (CIC). It has been previously described that the deletion in chromosome 6p22.3-p24.3, which harbors ATXN1, is associated with developmental delay and ASD [77,78]. Moreover, alteration of the ATXN1-CIC complex determines a spectrum of neurobehavioral phenotypes, including intellectual disability, attention deficit/hyperactivity disorder (ADHD) and autism spectrum disorder [79].…”
Section: Discussionmentioning
confidence: 99%
“…The pleiotropic function of JARID2 has been confirmed by the various phenotypes reported, especially regarding the neural and cardiac systems. Jumonji was originally found to be expressed in the brain of developing mice, and several recent reports have linked JARID2 and intellectual disability in human patients: deletions in chromosome 6p22‐p24, which include JARID2, are clinically linked with neurodevelopment disorders . Further characterization is required to understand whether these clinical observations may be explained at a molecular level by association of PRC2 with JARID2.…”
Section: Jarid2mentioning
confidence: 99%